Technology for manufacture of sugar free Kulfi using sucralose - Gokalbhai, Patel Hasmukhbhai (Indian Journal of Dairy Science, 2017)
A study was carried out to assess the replacement of sugar by intense sweetener sucralose in manufacture of sugar free Kulfi mix. Bulk of sugar was replaced by varying levels of bulking ingredients polydextrose (PD) and sorbitol (SO) while maltodextrin (MD) was kept constant @ 3% in combinations with varying levels of sucralose (SU) to impart similar sweetness viz. T1. (2% PD, 14% SO, 13.33 g/100 Kg Kulfi mix, SU), T2 (4% PD, 11% SO, 15.80g/100 Kg Kulfi mix, SU), T3 (6% PD, 9% SO, 17.50g/100 Kg Kulfi mix, SU), T4 (8% PD, 6% SO, 20.0g/100 Kg Kulfi mix, SU), T5 (9% PD, 4% SO, 21.66 g/100 Kg Kulfi mix, SU) and T6 (11% PD, 2% SO, 23.33g/100 Kg Kulfi mix, SU). Except viscosity, all the physico-chemical and compositional values remained statistically (p≤0.05) at par. Body and texture score was significantly affected, while other sensory attributes were unaffected in Kulfi mix. Thus, best bulking ingredients combination along with sucralose was polydextrose @ 9.0%, sorbitol @ 4.0% and maltodextrin @ 3.0% and sucralose @ 21.66 g/100 Kg Kulfi mix. Sugar free Kulfi thus prepared was compared with market Kulfi and control Kulfi, with sucrose as sweetening agent. Sensorily, control and sugar free Kulfi were statistically at par, and better than market Kulfi.